PyMem: A Graphical User Interface Tool for Neuromemristive Hardware–Software Co-Design - Aswani Radhakrishnan; Jushnah Palliyalil; Sreeja Babu; Anuar Dorzhigulov; Alex James (IEEE Open Journal of the Industrial Electronics Society)
The hardware implementation of neuromorphic system requires energy and area-efficient hardware. Memristor-based hardware architectures is a promising approach that naturally mimics the switching behavior of the neuron models. However, to build complex neural systems, it is a tedious process to select the right memristor models and architectures that are suitable to be used in a range of realistic conditions. To simplify the design and development of neuromemristive architectures, we present a web-based graphical user interface (GUI) called “PyMem” that uses Keras Python to implement multiple memristor models on multiple neural architectures that can be used to analyze their working under a wide range of hardware variability. Without the need for programming, the GUI provides options for adding variability to the memristors and observing the neural network behavior under realistic conditions. The tool has options to characterize the ideal (software) and nonideal (hardware) for performance analysis including accuracy, precision, recall, and relative current error values.